2018
DOI: 10.1161/circep.117.005831
|View full text |Cite
|
Sign up to set email alerts
|

Novel Measure of Local Impedance Predicts Catheter–Tissue Contact and Lesion Formation

Abstract: LI recorded from miniature electrodes provides a valuable measure of catheter-tissue coupling, and ΔLI is predictive of lesion formation during radiofrequency ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(155 citation statements)
references
References 18 publications
10
144
1
Order By: Relevance
“…Albeit baseline LI is in general lower than baseline GI, impedance drop during RFC‐application is higher for LI than for GI. This finding is in line with initial experimental studies and early clinical data . We showed a correlation of ΔLI with baseline LI, albeit with a low correlation coefficient, which is most likely attributable to heterogenities of ventricular myocardial tissue.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Albeit baseline LI is in general lower than baseline GI, impedance drop during RFC‐application is higher for LI than for GI. This finding is in line with initial experimental studies and early clinical data . We showed a correlation of ΔLI with baseline LI, albeit with a low correlation coefficient, which is most likely attributable to heterogenities of ventricular myocardial tissue.…”
Section: Discussionsupporting
confidence: 91%
“…Discrimination of healthy and scarred tissue using LI was initially demonstrated in acute and chronic models of myocardial infarction . More than two decades later, translation of experimental findings to early clinical experience using an ablation catheter incorporating LI measurements has recently been reported . Here, we demonstrate that LI can identify areas of scar in patients with VT.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, it should be acknowledged that contact force is not without limitations and it entails a higher cost; contact force does not take into consideration tissue characteristics or catheter stability. A recent study found that local impedance had a superior fit to lesion dimension than models that incorporated force time integral [14]. Thus, it is worth exploring if other parameters could also be of value in determining a successful lesion.…”
Section: Pre-ablation Parameters and Transmural Lesionsmentioning
confidence: 99%
“…Intracardiac echocardiography has been used in some studies, but it was found unable to precisely delineate lesion dimensions [15]. Generator impedance drop has been shown to correlate poorly with lesion depth and even worse with lesion diameter [14]. Local impedance appears to be a reliable indicator of lesion formation [14] but was not available at the time of the study.…”
Section: Limitationsmentioning
confidence: 99%